Global Prevalence of Domestic Cat Hepadnavirus: An Emerging Threat to Cats’ Health? - Shofa, Maya; Kaneko, Yasuyuki; Takahashi, Kazuki; Okabayashi, Tamaki; Saito, Akatsuki (Frontiers in Microbiology, 2022)
Hepatitis B is an infectious hepatocellular disease of global concern caused by hepatitis B virus (HBV), which belongs to Hepadnaviridae. Recently, a novel HBV-like virus, domestic cat hepadnavirus (DCH), was detected from an immunocompromised cat with a hepatic disease in Australia. Subsequent molecular investigation by independent research groups revealed that its prevalence rates were 6.5% in Australia, 10.8% in Italy, 12.4% in Thailand, 12.3% in Malaysia, 3.08% in United Kingdom, and 0.78% in Japan. Although the correlation between DCH infection and hepatic diseases remains to be elucidated, understanding the diversity of circulating DCH will contribute to its prevention and control in domestic cats. Herein, we summarize the current epidemiological data of DCH in these countries.